CAPAIAN TINGKAT PROFESIONALISME GURU PADA SMP DAN MTs KOTA PAYAKUMBUH - Adnan, Aryadie (TINGKAP, 2016)
ABSTRACTThis is an evaluative study to determine the achievement level of professionalism of teachers at the basic education level in Payakumbuh City. The study was deemed necessary given the low ability of teachers in the mastery of the material and the ability to teach, so the impact on the quality of learners. The study population is all teachers at the basic education level, namely SD, MI, SMP and MTs in Payakumbuh City. Sampling was determined with a technique of stratified purposive sampling with key person is a teacher who has been carrying out UKG at Human Resources Ministry of Education and Culture. The data was collected by way of documentation on the results of the study and implementation of the UKG test of teachers chosen to be sampled in MI and MTs. Documentation studies were also conducted on the data of teachers in the Education Office Payakumbuh about the background and qualifications of teacher education. Data was analyzed using descriptive analysis is to amend the total score obtained into percentages, classifying outcomes based on data obtained in five categories: Very Good, Good, Average, Poor and Very Poor The result of this study indicated that the achievement level of professionalism of teachers in SD and MI Payakumbuh is still in very low level, the average is around 49.51. This value indicates the performance level of professionalism of teachers in the category of very low. For Junior Secondary teachers, the average values is 40.71. This value indicates the performance level of professionalism of teachers is also in the very low category.Keywords: Teacher, professionalism, achievement